(untitled) (Research, Society and Development, 2023)
Immature permanent teeth with pulp necrosis are still a great challenge for endodontics. Traditionally these cases were treated through apexification using calcium hydroxide, however this treatment was long and caused the weakening of the dental roots. In recent years, through much research, the option of pulpal revascularization has emerged. This work aims to elaborate an information cluster about the technique of pulpal revascularization, which can serve as a basis for both academics and professionals in the field of dentistry. For the development of this work, a review of the narrative literature was carried out using as a bibliographic base scientific articles about the proposed theme, published between 2000 and 2022; available in the online databases BVSalud, PUBMed, Lilacs, Scielo and Google Scholars. presented in Portuguese and English. At the end of this work it was possible to conclude that currently the pulp revascularization technique is efficient in the treatment of immature permanent teeth with pulp necrosis. Even today, there is no single protocol considered ideal, several protocols are found in the literature demonstrating positive results.